AA amyloidosis as a complication of primary lymphedema. (March 2014) - Beloncle, François; Sayegh, Johnny; Eymerit-Morin, Caroline; Duveau, Agnès; Augusto, Jean-François
Abstract Primary lymphedema is a rare disease caused by a disorder of lymphangiogenesis. Clinical presentation and age at onset are variable. AA amyloidosis is usually due to chronic inflammatory diseases, malignant tumors or less frequently chronic infectious diseases. We report here the first two cases of AA amyloidosis present with renal failure and nephrotic syndrome in patients with primary lymphedema-induced chronic leg ulcers. The first patient was a 62-year-old female who presented with chronic untreated leg ulcers for 8 years secondary to primary lymphedema. A kidney biopsy done for nephrotic syndrome allowed the diagnosis of AA amyloidosis. The second patient was a 54-year-old male who presented with hereditary lymphedema and elephantiasis since the age of 12. A salivary gland biopsy allowed the diagnosis of AA amyloidosis. Renal function deteriorated progressively needing chronic haemodialysis. Chronic leg ulcers have been rarely reported to induce AA amyloidosis. Only five other cases have been reported in the literature, but none of them with chronic lymphedema. We believe that the relation between lymphedema, chronic leg ulcers and AA amyloidosis is underestimated.